The relationship of training methods in NCAA Division I cross-country runners and 10,000-meter performance - Kurz, M. J.; Berg, K.; Latin, R.; deGraw, W. (The Journal of Strength and Conditioning Research, 2000)
The purpose of this study was to evaluate the relationship between training methods of NCAA Division I runners and 10,000-m performance. Fourteen qualifying teams of the National Collegiate Athletic Association Division I national cross-country meet and 16 randomly chosen, nonqualifying teams participated in the study. A survey was used to evaluate the training methods of the respective teams throughout the training season. The results of the study indicated that the use of speed work, fartlek, mileage, and running twice a day during the transition phase of training were associated with a slower team performance. Interval training and fartleks during the competition phase were related to a slower team performance. Intervals and tempo training during the peaking period were related to a better performance. The multiple regression equation revealed that hill training during the transition phase was related to a faster team time. The transition phase of training appears to be related to success at the end of the season. (The Journal of Strength & Conditioning Research: Vol. 14, No. 2, pp. 196-201)